Supply side management in microhydro using battery bank: A case study of Pinthali microhydro plant, Kavre - Subedi, Amit; Bajracharya, Tri Ratna (Journal of Innovations in Engineering Education, 2021)
Geographical difficulties and slow development of power generation, transmission and distribution, related activities have made many remote areas not assessable to national grids in Nepal. Electricity demand is increasing day by day in urban as well as rural areas but instant extension of national grid seems difficult in many remote places of Nepal. Thousands of Micro hydropower are being installed throughout the country where extension of grid is difficult. This paper presents the introduction of battery bank for the supply side management in the micro hydropower plants. Surplus power during off load time is stored in a battery instead of wasting in dump load. The system is designed in Matlab Simulink where system containing Electronic Load Controller(ELC), Battery Management System(BMS), three phase ac/dc converter were used. Synchronous Generator which generates constant power feeds the load, battery and dump load according to requirement. Battery uses the power for charging during off load hour and supplies deficit power during peak hour. Case study of Pinthali microhydro power of capacity 8.1 KW was carried out for load survey to calculate excess power. Simulated system was able to distribute the power to load when load demand was higher than generation through the battery.